Harnessing Raman Spectroscopy for Enhanced Bioprocess Monitoring: Predictive CO2 Analysis and Robust pH Determination in Bioreactor Off-Gas Stream - Tobias Wallocha; Michaela Poth (Fermentation, 2025)
The accurate measurement of CO2 concentration in fermentation off-gas is crucial for monitoring and optimizing bioprocesses, particularly in mammalian cell cultures. In this study, we successfully utilized Raman off-gas spectroscopy to achieve time-resolved prediction of CO2 concentrations in the fermentation off-gas. Our experiments were conducted using two different media: a commercial medium (medium 1) and an in-house Roche medium (medium 2), each tested with two different lots. The results demonstrated that Raman spectroscopy provides precise and real-time CO2 measurements, which are essential for effective process monitoring and control. Furthermore, we established that CO2 off-gas analysis can be directly correlated with the pH value of the fermentation medium. This correlation allows for accurate pH prediction with comparable precision to traditional methods, where CO2 levels are first determined via Raman spectroscopy or an off-gas analyzer and then used to infer pH through a correlation curve. In the final step of our study, we employed a Raman submers probe to predict CO2 and pH directly within the fermentation medium. Compared to the model accuracy in the off-gas stream, the performance of the Raman submers probe in predicting CO2 and pH within the medium was significantly worse, likely due to the absence of a pretrained model for CO2. Our findings highlight the potential of Raman off-gas spectroscopy as a powerful tool for real-time bioprocess monitoring and control, offering significant advantages in terms of accuracy and efficiency.